SIKAP DAN PARTISIPASI POLITIK MAHASISWA KOTA PEKANBARU TERKAIT DUKUNGAN PRESIDEN DALAM PENGESAHAN REVISI UNDANG-UNDANG KOMISI PEMBERANTASAN KORUPSI TAHUN 2019 - Siregar, Jhoni Fernando; ", Adlin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
In 2019 there was a phenomenon where the President of the Republic of Indonesia supported the ratification of the revision KPK Law of 2002 to Law Number 19 of 2019 concerning the KPK. Students and the public who disagreed with the president's support for the ratification held a demonstration to ask the president to issue a perppu, however, the president rejected this, but there was a decline after the ratification of the revision of the KPK Law. The formulation of problem questions, namely: 1) Where is the Position of Pekanbaru City Students Based on the Criteria given by Paige in the Concept of Political Participation in the Ramlan Surbakti Book ?; 2) Where is the Position of Pekanbaru City Students Among the 4 Forms of Apathy?. The research objectives were: (1) To determine the position of Pekanbaru City students based on the criteria given by Paige from the two factors that influenced the levels of political participation in the book of Ramlan Surbakti; (2) To determine the position of Pekanbaru City students among the 4 forms of apathy. This study uses a "mixed" research approach. The data collection technique is done by distributing questionnaires and followed by interviews. The results showed that: 1) Pekanbaru City students are in a 'radical militant' position with the criteria of high political awareness and low trust in the political system; 2) Pekanbaru City students are in an anomic position based on 4 forms of apathy.Â Keywords: Attitudes of Pekanbaru City Students, Political Participation, Demonstrations, Law no. 19 of 2019 concerning the Corruption Eradication Commission, apathy